2006
DOI: 10.1302/0301-620x.88b7.17671
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the anterior cruciate ligament using the polyester ABC ligament scaffold

Abstract: We carried out a prospective study of 71 patients who had undergone reconstruction of the anterior cruciate ligament with the ABC scaffold. Their mean age was 28 years (18 to 50). All had either sub-acute or chronic traumatic deficiency of the ligament. The mean period of follow-up was five years (four to seven). Assessment included the use of the International Knee Documentation Committee score, the modified Lysholm score, the Tegner Activity score, the Knee Injury and Osteoarthritis Outcome score and measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
2
6
0
2
Order By: Relevance
“…Our results were markedly different, with a 42% failure rate at a mean follow-up of 5.1 years. We cannot readily explain the significant differences between our study and that by Petrou et al, 45 but our results are similar to those of Jadeja et al 23 …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our results were markedly different, with a 42% failure rate at a mean follow-up of 5.1 years. We cannot readily explain the significant differences between our study and that by Petrou et al, 45 but our results are similar to those of Jadeja et al 23 …”
Section: Discussionsupporting
confidence: 71%
“…Petrou et al 45 reported on a series of ABC ligaments placed using the newer instruments via an arthrotomy and an accelerated rehabilitation program. They found a survival rate of 100% at follow-up of 4 to 7 years.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven articles were identified with greater than 4‐year outcomes for other PET grafts 13–23 (seven Leeds‐Keio grafts, two ABC Surgicraft, one Proflex and one Ligastic) shown in Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…There were no failures and only two patients suffered from recurrent synovitis. 169 The advantage of tissue-engineered ligament is that it does not elicit a permanent foreign body reaction, as it is gradually reabsorbed and replaced by natural tissue. In contrast to the permanent synthetic prosthesis which loses strength with time, the mechanical behavior of tissue-engineering grafts should improve with time because of neoligament tissue development and remodelling.…”
Section: Tissue Engineering and Scaffoldsmentioning
confidence: 99%